Digitalization Of Payments In Public Financial Management: Efficiency And Transparency Strategy - Suryanto Suryanto; R. Ratna Meisa Dai (Jurnal Agregasi, 2025)
Digital transformation in the public sector drives innovation in state financial management, including implementing digital payment systems. This study aims to analyze the contribution of payment digitization to the efficiency and transparency of public finances in Indonesia. The method used is qualitative through content analysis and case studies, with primary data from interviews and secondary data from policy documents and scientific literature. The study results show that the implementation of Digipay and SP2D Online significantly impacts administrative efficiency, transaction acceleration, and strengthening control. Digitalization also increases transparency through real-time transaction tracking and supports open audits. However, challenges remain regarding interoperability, data security, and human resources. Overall, digitalization is an important strategy in public finance reform. The implications of this research suggest that the success of payment digitalization can serve as a model to accelerate broader state financial governance reforms and encourage the adoption of similar technologies in other public sectors.